Role of intermolecular forces on surfactant-steam performance into heavy oil reservoirs - Seng, L.Y. (Society of Petroleum Engineers (SPE), 2020)
This study investigates the role of heavy oil polar fractions in surfactant-steam flooding performance. Performance analyses were done by examination of the dipole-dipole and ion-ion interactions between polar head group of surfactants and charged polar fraction of crude oil, asphaltenes. Surfactants are designed to reduce the interfacial tension between two immiscible fluids (such as oil and water) and effectively used for oil recovery. They reduce the interfacial tension by aligning themselves at the interface of these two immiscible fluids, this way, their polar head group can stay in water and non-polar tail can stay in oil phase. However, in heavy oil, the crude oil itself has high amount of polar components (mainly asphaltenes). Moreover, polar head group in surfactants is charged and the asphaltene fraction of crude oils carry reservoir rock components with charges. The impact of these intermolecular forces on surfactant-steam process performance was investigated with 10 coreflood experiments on an extra-heavy crude oil. 9 surfactants (3 anionic, 3 cationic and 3 nonionic surfactants) were tested. Results of each coreflood test were analyzed through cumulative oil recovery and residual oil content. The performance differences were evaluated by polarity determination through dielectric constant measurements and by ionic charges through zeta potential measurements on asphaltenes fraction of produced oil and residual oil samples. The differences in each group of surfactant tested in this study are the tail length. Results indicate that longer hydrocarbon tail yielded higher cumulative oil recovery. Based on the charge groups present in the polar head of surfactants anionic surfactants resulted in higher oil recovery. The further examinations on asphaltenes from produced and residual oils show that the dielectric constants of asphaltenes originated from the produced oil gives higher polarity for surfactant-steam experiments conducted with longer tail length, which provide information on polarity of asphaltenes. The ion-ion interaction between produced oil asphaltenes and surfactant head groups were determined through zeta potential measurements. For the most successful surfactant-steam processes, these results showed that the changes on asphaltenes surface charges getting lower with the increase in oil recovery, which indicates that once asphaltenes are interacting more with polar head of surfactants, then, the recovery rate increases. Our study shows that surfactant-steam flooding performance in heavy oil reservoirs controlled by the interaction between asphaltenes and polar head group of surfactants. Accordingly, main mechanism which controls the effectiveness of process is the ion-ion interaction between the charges in asphaltene surfaces and polar head group of crude oils. Since crude oils carry mostly negatively charged reservoir rock particles, our study suggests the use of anionic surfactants for the extraction of heavy oils. Â© Copyright 2020, Society of Petroleum Engineers